2003
DOI: 10.1143/jjap.42.2193
|View full text |Cite
|
Sign up to set email alerts
|

Behavior of Plated Microbumps during Ultrasonic Flip-Chip Bonding Determined from Dynamic Strain Measurement

Abstract: The effect of moderate viscosity is of the same type for sound waves and for surface waves striking.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…Among the various forms of the SiP, the stacked three-dimensional SiP, which forms penetrating electrodes through the chip and connects the upper and lower chips by narrow-pitch bumps of Au or Cu, is suited for high-speed operation, and thus has been actively studied [5][6][7]. In a three-dimensional stacked SiP, the chips to be stacked should be thinned to a thickness of several dozen micrometers, considering the wiring resistance of the penetrating electrode and the height of the package.…”
Section: Introductionmentioning
confidence: 99%
“…Among the various forms of the SiP, the stacked three-dimensional SiP, which forms penetrating electrodes through the chip and connects the upper and lower chips by narrow-pitch bumps of Au or Cu, is suited for high-speed operation, and thus has been actively studied [5][6][7]. In a three-dimensional stacked SiP, the chips to be stacked should be thinned to a thickness of several dozen micrometers, considering the wiring resistance of the penetrating electrode and the height of the package.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 2(b) shows a cross section of the strain sensor. On the basis of the previous publications, 21,22) the strain sensor has been designed such that it can determine strains along the axis parallel to the direction of ultrasonic vibration and the axis normal to the surface, i.e., in the direction of pressing load. The sensor is composed of a pair of n-and p-type piezoresistance gauges.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…The problem is that an actual bonding surface consists of an oxide film and a machined layer; [3][4][5][6][7] therefore, adhesion between surfaces at the bond interface and removal of the oxide film represent necessary requirements to obtain high bond strength. Recently, ultrasonic vibration, [8][9][10][11][12][13] plasma processing, [14][15][16][17][18][19] and organic acid pretreatment [20][21][22][23] have been investigated as methods for breaking and cleaning a superficial oxide film. Indeed, in a previous study, we showed that modification of an oxide film with formic acid greatly improves the strength of bonding between tin surfaces 22) and between tin and copper.…”
Section: Introductionmentioning
confidence: 99%